Description of a new soft tick species (Acari: Argasidae: Ornithodoros) parasite of Octodon degus (Rodentia: Octodontidae) in northern Chile - Muñoz-Leal, Sebastian; Venzal, José Manuel; Nava, Santiago; Marcili, Arlei; González-Acuña, Daniel; Martins, Thiago F.; Labruna, Marcelo B. (Elsevier, 2020)
A new argasid (Argasidae) tick is herein described based on morphology and molecular data obtained from larvae parasitizing Octodon degus and from ticks collected inside burrows in northern Chile. Unfed laboratory-reared larvae were mounted in slides for morphometrical and morphological analyses. Larvae of Ornithodoros octodontus n. sp. share morphological traits with Ornithodoros quilinensis and Ornithodoros xerophylus, two species associated with rodents in the Argentinean Chaco. However, a longer hypostome with two rows of 21 and 22 denticles each one, and conspicuous leaf-shaped anal plates separate O. octodontus. While nymphal stages of O. octodontus lack cheeks and possess a micromammillated dorsal integument, adults have cheeks and exhibit markedly irregular mammillae along their dorsal surface. Phylogenetic analyses of neotropical Argasidae based on mitochondrial 16S rDNA sequences point that O. octodontus forms a monophyletic group with O. xerophylus and an unidentified Ornithodoros sp. from Bolivia, all of them associated with burrow-dweller rodents. Ornithodoros aragaoi and Ornithodoros davisi, two rare species collected once only in the Peruvian Andean Plateau during 1955 are morphologically closely related with adults and nymphs of O. octodontus. Biological observations of O. octodontus revealed autogenic females. For the moment, subgeneric classification of this new species depends on further biological studies. The fauna of ticks occurring in Chile is now represented by 22 species, 11 belonging to the Argasidae family.